2023
DOI: 10.1021/jacs.2c13086
|View full text |Cite
|
Sign up to set email alerts
|

Direct Incorporation of Dinitrogen into an Aliphatic C–H Bond

Abstract: The activation of dinitrogen (N 2 ) and direct incorporation of its N atom into C−H bonds to create aliphatic C−N compounds remains unresolved. Incompatible conditions between dinitrogen reduction and C−H functionalization make this process extremely challenging. Herein, we report the first example of dinitrogen insertion into an aliphatic Csp 3 −H bond on the ligand scaffold of a 1,3-propane-bridged [N 2 N] 2− -type dititanium complex. Mechanistic investigations on the behaviors of dinuclear and mononuclear T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The design of novel [N 2 N] 2– -type dinuclear and trinuclear Ti–N 2 complexes by Shi and co-workers highlights the ongoing efforts to develop new catalysts for nitrogen fixation. Unprecedented N 2 fixation and insertion into aliphatic hydrocarbon in one pot via a bimetallic system were first discovered and reported in 2023 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of novel [N 2 N] 2– -type dinuclear and trinuclear Ti–N 2 complexes by Shi and co-workers highlights the ongoing efforts to develop new catalysts for nitrogen fixation. Unprecedented N 2 fixation and insertion into aliphatic hydrocarbon in one pot via a bimetallic system were first discovered and reported in 2023 …”
Section: Introductionmentioning
confidence: 99%
“…Unprecedented N 2 fixation and insertion into aliphatic hydrocarbon in one pot via a bimetallic system were first discovered and reported in 2023. 30 With the vigorous development of the coordination chemistry of this simple molecule, dinitrogen complexes exhibit a variety of binding modes. It is interesting to know that dinitrogen can be fixed on the single metal site of transition metal complexes through end-on or side-on configuration and that the monometallic end-on coordination mode is more common than the monometallic side-on coordination mode (Figure 1, left).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Research conducted by techno‐economic modeling has indicated that it is imperative to develop PEC water electrolysis cells with an efficiency higher than 10 % and stability of more than 10 years to compete with conventional methane steam reforming [37–42] . Since the PEC performances of photoelectrodes are influenced by the electron‐hole pair generation, separation, transport, and surface reaction, the loss of photo‐induced charge carriers in these processes should be suppressed [43–46] . In this respect, it is required to develop highly active catalysts, charge transport layers, as well as passivation layers.…”
Section: Introductionmentioning
confidence: 99%
“…3 Solar power, utilized for electrochemical or photoelectrochemical water splitting, is the largest source of renewable energy by far and has attracted considerable research interest. [4][5][6][7] Therefore, renewable energy-powered water electrolysis, so-called green hydrogen production, should be the focus of the next decade.…”
Section: Introductionmentioning
confidence: 99%